Precious metal alloy nano-enzyme as well as preparation method and application thereof
By using weakly oxidized porous silicon nanoparticle support to deposit palladium-platinum precious metal alloy nanoenzymes in situ, the problems of complex synthesis and catalytic performance of precious metal alloy nanoenzymes in the prior art are solved, and a high-activity and biodegradable support nanoenzymes are achieved, which significantly inhibits the development of tumors.
Patent Information
- Application Number
- CN202411979036.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing synthesis methods of precious metal alloy nanoenzymes are complex and require high temperature conditions, which leads to the decline of nanoparticle agglomeration and catalytic performance. At the same time, the removal and metabolism problems in organisms have not been effectively solved.
Weak oxidized porous silicon nanoparticles are used as support to deposit palladium-platinum precious metal alloy nanoenzymes through in-situ reduction reaction to form a supported precious metal alloy nanoenzymes, which improves its catalytic activity and bioavailability.
The uniform dispersion and high activity of precious metal alloy nanoenzymes has been achieved, with excellent storage stability and biodegradability in vivo, significantly inhibiting the development of tumors.
Smart Images

Figure HDA0005224182750000011 
Figure HDA0005224182750000012 
Figure HDA0005224182750000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanozymes and tumor treatment, and in particular to a noble metal alloy nanozyme and a preparation method and application thereof. Background Art
[0002] Photothermal therapy (PTT) is a physical therapy with spatiotemporal controllable properties. PTT converts near-infrared light energy into thermal energy through photothermal agents to ablate tumors. Compared with traditional photothermal therapy (>50°C), mild photothermal therapy (m-PTT) has greater advantages in reducing treatment side effects and improving patient comfort. m-PTT usually increases the local temperature of the tumor to 38-43°C to induce cancer cell death while preventing high thermal damage to surrounding normal tissues. However, mild photothermal irradiation usually leads to overexpression of heat shock proteins (HSPs), which promote protein refolding and repair of thermal protein damage, thereby enhancing the thermal resistance of tumor cells to m-PTT. To solve this problem, several small molecule inhibitors of heat shock proteins (17-AGG, quercetin, OGX-427, etc.) have been developed. However, high biological toxicity, low selectivity and drug resistance limit the clinical transformation of these HSPs inhibitors. Therefore, finding effective methods to inhibit the expression of HSPs is crucial to improve the efficacy and competitiveness of m-PTT in cancer treatment.
[0003] Nanozymes are nanoformulations with reaction kinetics and catalytic properties similar to those of natural enzymes. Nanozymes can inhibit the expression of HSPs. Therefore, they provide a feasible way to promote m-PTT. Specifically, peroxidase-like (POD) nanozymes can decompose endogenous hydrogen peroxide (H2O2) in the tumor microenvironment (TME) and produce reactive oxygen species (ROS), thereby achieving the purpose of cleaving HSPs. In addition, nanozymes with peroxidase-mimicking (POD) and glutathione oxidase-mimicking (GSHOx) activities can induce ROS generation and deplete the antioxidant glutathione (GSH) in the TME. The above process ultimately leads to the occurrence of ferroptosis characterized by the accumulation of lipid peroxides (LPO). A large amount of LPO accumulation can further generate aldehyde products (such as malondialdehyde), which react with the amino acid residues of HSPs molecules, resulting in the denaturation of HSPs. Among them, compared with single metal nanozymes, precious metal alloy nanozymes have an alloying effect, a more reasonable electron density distribution, and richer catalytic sites. Platinum (Pt) can be alloyed with other metals (such as ruthenium, palladium, gold, silver and titanium) to effectively adjust the electronic structure and optimize the catalytic performance. The prior art discloses a palladium-platinum alloy nanozyme that can induce tumor ferroptosis. At the same time, PdPt nanozyme has activities similar to catalase (CAT) and oxidase (OXD), which can convert H2O2 into oxygen (O2), thereby reversing the hypoxic state in tumor tissues, and then oxidize O2 into ROS to kill tumor cells.
[0004] However, the synthesis methods of most alloy nanozymes in the prior art require the introduction of high temperature conditions, which complicates the preparation process. High temperature treatment usually requires special equipment and strict temperature control procedures, which not only increases the experimental difficulty requirements, but also may cause the agglomeration or grain growth of nanoparticles, affecting the uniformity and catalytic performance of the product. The chemical reduction process depends on the addition of reducing agents such as hydrogen, sodium borohydride or ascorbic acid, which may produce by-products on or around the surface of nanoparticles while reducing the noble metal ions, affecting the purity and activity of the final synthetic product. In addition, since the surface energy of noble metal alloy nanozymes is very high, it is easy to agglomerate, resulting in a sharp drop in catalytic activity.
[0005] Therefore, we still need to use noble metal alloy nanozymes to develop dual-mode anti-tumor pathways of ferroptosis and m-PTT to seek the best option for strengthening m-PTT. In addition, due to the high surface energy of noble metal alloy nanozymes, they are prone to agglomeration, resulting in a sharp decrease in catalytic activity. The clearance and metabolism of noble metal alloy nanozymes larger than 5nm in vivo should also be considered.
[0006] The use of carriers not only ensures the dispersion of precious metal alloy nanozymes, but also improves their bioavailability. Electrochemically etched porous silicon (PSi) is a carrier with rich pore structure and surface modification possibilities. It can be used as a carrier to enhance the catalytic performance of dual nanozymes through pore confinement effects. In addition, the PSi carrier has good biodegradability, allowing the loaded nanozymes to be effectively metabolized and excreted from the body. Currently, PSi-based complexes have been widely used in biomedical fields such as sensor monitoring, antibacterial wound therapy, and tumor treatment.
[0007] Therefore, it is of great significance to study and develop a new type of precious metal alloy nanozyme for tumor treatment. Summary of the invention
[0008] In view of this, the technical problem to be solved by the present invention is to provide a noble metal alloy nanozyme and a preparation method and application thereof. The noble metal alloy nanozyme is uniformly dispersed, has good quadruple nanozyme activity (CAT-like, OXD-like, POD-like, GSHox-like), storage stability, and excellent in vivo degradation ability and biosafety.
[0009] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] The present invention provides a loaded noble metal alloy nanozyme, which is composed of weakly oxidized porous silicon nanoparticles and noble metal alloy nanozymes loaded on the surface and in the pores of the nanoparticles;
[0011] The weakly oxidized porous silicon nanoparticles are obtained by oxidizing porous silicon nanoparticles through phosphate buffer solution, deionized water, alkaline borate or phosphate solution.
[0012] The weakly oxidized porous silicon nanoparticles serve as a new type of carrier and reducing agent for nanozyme precursors. Through the pore confinement effect, the adsorption capacity of the noble metal alloy nanozymes distributed inside the pores for the substrate is improved, thereby promoting the catalysis of the substrate.
[0013] Preferably, the noble metal alloy nanozyme is selected from palladium-platinum noble metal alloy nanozyme, gold-silver noble metal alloy nanozyme or silver-palladium noble metal alloy nanozyme; more preferably, it is palladium-platinum noble metal alloy nanozyme.
[0014] A tight semiconductor-metal heterointerface is formed between the noble metal alloy nanozyme in the loaded noble metal alloy nanozyme and the Si-OH bonds on the surface of the weakly oxidized porous silicon nanoparticles, which promotes electron-hole separation and thus significantly improves the activity of the loaded noble metal alloy nanozyme.
[0015] Moreover, the unique nanopore structure of weakly oxidized porous silicon nanoparticles can improve the interaction between the reaction substrate and the noble metal alloy nanozyme, enhance the catalytic performance of the noble metal alloy nanozyme, and further enhance the simulated activity of the loaded noble metal alloy nanozyme under mild photothermal stimulation.
[0016] Preferably, the noble metal alloy nanozyme is selected from palladium-platinum noble metal alloy nanozyme, and the Pd content in the weakly oxidized porous silicon of the supported noble metal alloy nanozyme is 80-85 μg / mg, and the Pt content is 35-50 μg / mg. In some specific embodiments of the present invention, the Pd content in the weakly oxidized porous silicon is 84.13±0.2117 μg / mg, and the Pt content is 39.18±0.3023 μg / mg by inductively coupled plasma spectroscopy (ICP-OES).
[0017] Preferably, in the present invention, the mass ratio of palladium to platinum in the palladium-platinum alloy nanozyme is (2-2.5):1, more preferably (2.1-2.2):1.
[0018] The present invention also provides a method for preparing the above-mentioned supported noble metal alloy nanozyme, comprising the following steps:
[0019] (1) mixing porous silicon nanoparticles and phosphate buffer solution to obtain weakly oxidized porous silicon nanoparticles;
[0020] (2) A palladium source, a platinum source, weakly oxidized porous silicon nanoparticles and water are mixed to perform an in-situ reduction reaction to obtain the loaded noble metal alloy nanozyme.
[0021] The present invention utilizes the mild reduction activity of Si-OH bonds rich in the surface of weakly oxidized porous silicon nanoparticles to obtain the loaded noble metal alloy nanozyme by one-step in-situ reduction deposition, so that the noble metal alloy nanozyme is highly evenly dispersed on the surface of weakly oxidized porous silicon nanoparticles.
[0022] Preferably, the pH value of the phosphate buffer solution is 7-7.4.
[0023] Preferably, the ratio of the porous silicon nanoparticles to the phosphate buffer solution is 1 g: (10-300) mL; more preferably 1 g: 100 mL.
[0024] Preferably, the reaction temperature in step (1) is 25°C-50°C; more preferably 37°C.
[0025] Preferably, in the present invention, the molar ratio of the palladium element in the palladium source to the platinum element in the platinum source is 1:(0.5-1.5); more preferably 1:(0.8-1.2); further preferably 1:1.
[0026] Preferably, the palladium source is selected from one or more of chloropalladic acid, palladium chloride, and sodium chloropalladate; more preferably, chloropalladic acid.
[0027] Preferably, the platinum source is selected from one or more of chloroplatinic acid, potassium chloroplatinate, and ammonium chloroplatinate; more preferably, chloropalladic acid.
[0028] The present invention also provides the use of the above-mentioned loaded noble metal alloy nanozyme or the loaded noble metal alloy nanozyme prepared by the above-mentioned preparation method in the preparation of tumor treating drugs.
[0029] The tumor treatment drugs include but are not limited to nanocatalytic tumor treatment drugs and photothermal tumor treatment drugs.
[0030] The photothermal therapy drug for treating tumors can effectively exert the therapeutic effect of mild photothermal therapy (m-PTT) by inhibiting the expression of HSPs.
[0031] The loaded noble metal alloy nanozyme of the present invention or the loaded noble metal alloy nanozyme prepared by the above-mentioned preparation method reverses the hypoxic state in the tumor microenvironment by converting endogenous H2O2 into oxygen.
[0032] The loaded noble metal alloy nanozyme described in the present invention can also generate a large amount of active oxygen, consume the antioxidant glutathione, accumulate lipid peroxides, and ultimately induce iron allergy to inhibit the expression of HSPs.
[0033] Moreover, mild photothermal stimulation can enhance the ferroptosis process of the loaded noble metal alloy nanozyme, and ultimately significantly inhibit the development of tumors in vivo. In addition, the loaded noble metal alloy nanozyme of the present invention also has good storage stability and in vivo biodegradability, and has high biosafety.
[0034] Compared with the prior art, the supported noble metal alloy nanozyme provided by the present invention is composed of weakly oxidized porous silicon nanoparticles and noble metal alloy nanozymes loaded on the surface and in the pores thereof; the weakly oxidized porous silicon nanoparticles are obtained by oxidation of porous silicon nanoparticles by phosphate buffer solution, deionized water, alkaline borate or phosphate solution. The supported noble metal alloy nanozyme has excellent quadruple enzyme-mimicking activity (CAT-like, OXD-like, POD-like, GSHox-like), good storage stability and in vivo biodegradability, which is of great significance for tumor treatment, especially mild photothermal tumor treatment and nanocatalytic tumor treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the preparation of the weakly oxidized nanoporous silicon powder loaded with palladium-platinum alloy nanozyme prepared in Example 1;
[0036] Figure 2 The attenuated total reflection infrared spectra of different silicon materials (porous silicon, peroxidized porous silicon, weakly oxidized porous silicon PSi, silicon dioxide);
[0037] Figure 3 Transmission electron microscope (TEM) images of porous silicon loaded with palladium-platinum alloy nanozymes and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes;
[0038] Figure 4 Figure a is a photothermal response curve of the control group, porous silicon, weakly oxidized porous silicon, porous silicon loaded with palladium-platinum alloy nanozymes, and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes; Figure b is a photothermal response curve of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes after being irradiated with lasers of different current densities; Figure c is a temperature change curve of weakly oxidized porous silicon loaded with nanozymes after being exposed to five near-infrared light irradiation-cooling cycles;
[0039] Figure 5 Figure a shows the amount of oxygen produced after different materials react with H2O2 at 37°C for 5 minutes; Figure b shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as CAT-like under no near-infrared light; Figure c shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as CAT-like under near-infrared light; Figure d shows the double reciprocal curve of palladium-platinum alloy nanozyme as CAT-like without the weakly oxidized porous silicon carrier;
[0040] Figure 6 Figure a shows the amount of oxygen produced after different materials react with TMB at 37°C for 5 minutes; Figure b shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as OXD-like under conditions without near-infrared light; Figure c shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as OXD-like under conditions with near-infrared light; Figure d shows the double reciprocal curve of palladium-platinum alloy nanozyme as OXD-like after the weakly oxidized porous silicon carrier is removed;
[0041] Figure 7 Figure a shows the absorption spectra of different materials after reacting with H2O2 and TMB at 37°C for 5 minutes; Figure b shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as POD-like under the condition of no near-infrared light; Figure c shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as POD-like under the condition of near-infrared light; Figure d shows the double reciprocal curve of palladium-platinum alloy nanozyme as POD-like after removing the weakly oxidized porous silicon carrier;
[0042] Figure 8 Figure a shows the amount of oxygen produced after different materials react with GSH and DTNB at 37°C for 5 minutes; Figure b shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as GSHOx-like under conditions without near-infrared light; Figure c shows the double reciprocal curve of porous silicon loaded with palladium-platinum alloy nanozyme and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme as GSHOx-like under conditions with near-infrared light; Figure d shows the double reciprocal curve of palladium-platinum alloy nanozyme as GSHOx-like after the weakly oxidized porous silicon carrier is removed;
[0043] Fig. 9 Figure a is the electronic state density (DOS) diagram of the porous silicon supported by the palladium-platinum alloy nanozyme; Figure b is the electronic state density (DOS) diagram of the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme;
[0044] Fig.10 The cell viability graph of 4T1 cells after being treated with porous silicon, weakly oxidized porous silicon, porous silicon loaded with palladium-platinum alloy nanozymes, and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes at different concentrations under near-infrared light irradiation;
[0045] Fig.11 This is a diagram showing the oxygen production in 4T1 cells after different treatments using [Ru(dpp)3]Cl2 as a fluorescent probe;
[0046] Fig.12 This is a diagram showing the use of DCFH as a fluorescent probe to detect ROS generation in 4T1 cells after different treatments;
[0047] Fig.13 is the ratio of glutathione to oxidized glutathione in 4T1 cells after different treatments;
[0048] Fig.14 is the MDA level in 4T1 cells after different treatments;
[0049] Fig.15 Western blot bands of HSPs in 4T1 cells after different treatments;
[0050] Fig.16 The viability of 4T1 cells after exposure to freshly prepared PdPt alloy nanozymes loaded on weakly oxidized porous silicon or PdPt alloy nanozymes loaded on weakly oxidized porous silicon stored under dry conditions at room temperature for one month under near-infrared light irradiation;
[0051] Fig.17 It is the curve diagram of tumor volume changes in each group after different treatments;
[0052] Fig.18The accumulation of Pd (a), Pt (b), and Si (c) elements in major organs and tumors 1 day and 14 days after intratumoral injection of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes;
[0053] Fig.19 The results of H&E staining, Tunel staining, Ki-67 staining, HIF-1α and HSP70 staining of tumors in each group of tumor-bearing mice after different treatments. DETAILED DESCRIPTION
[0054] To further illustrate the present invention, a noble metal alloy nanozyme, a preparation method and an application thereof provided by the present invention are described in detail below in conjunction with embodiments.
[0055] Example 1
[0056] (1) Preparation of weakly oxidized porous silicon nanoparticles
[0057] Porous Silicon (PSi) thin film is prepared by electrochemical etching of silicon wafers.
[0058] First, the silicon wafer was placed in an etching solution containing hydrofluoric acid and 95% ethanol (v:v = 4:1), and then 2 The PSi film was then etched with a current density of 1.3% for 600 seconds. The PSi film was then etched with a 3.3% hydrofluoric acid-ethanol solution for 180 seconds to peel it off from the silicon substrate. The PSi film was then peeled off from the silicon substrate by etching with a 3.3% hydrofluoric acid-ethanol solution for 180 seconds. After ultrasonically crushing (500W) the PSi layer for 30 minutes, fresh porous silicon (PSi) nanoparticles were obtained. The PSi nanoparticles were placed in a PBS solution (pH = 7.4), shaken at 37°C for 2 hours, and then centrifuged (10000rpm, 10 minutes) to collect weakly oxidized porous silicon nanoparticles.
[0059] (2) Preparation of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0060] HPdCl4 (1.0 mM) and HPtCl6 (1.0 mM) were mixed and added to a weakly oxidized porous silicon nanoparticle aqueous solution (2.5 mg / mL). The solution was oscillated at room temperature for 10 minutes, then centrifuged at 10,000 rpm and washed with water three times to remove residual palladium (II) and platinum (IV), thereby obtaining a weakly oxidized porous silicon solution loaded with a palladium-platinum alloy nanozyme, and finally freeze-dried to obtain a weakly oxidized porous silicon powder loaded with a palladium-platinum alloy nanozyme (wherein, according to inductively coupled plasma spectroscopy (ICP-OES) analysis, the palladium loading was 84.13 ± 0.2117 μg / mg, the platinum loading was 39.18 ± 0.3023 μg / mg, and the mass ratio of palladium to platinum in the palladium-platinum alloy was 2.1:1), and the weakly oxidized porous silicon was the weakly oxidized porous silicon nanoparticles prepared in the above step (1).
[0061] Comparative Example 1
[0062] (1) First, place the silicon wafer in an etching solution containing hydrofluoric acid and 95% ethanol (v:v = 4:1), and then 2 The PSi film was then etched with a current density of 1.500 W for 600 seconds. The PSi film was then etched with a 3.3% hydrofluoric acid-ethanol solution for 180 seconds to peel it off from the silicon substrate. The PSi film was then peeled off from the silicon substrate by etching with a 3.3% hydrofluoric acid-ethanol solution for 180 seconds. After ultrasonically crushing (500 W) the PSi layer for 30 minutes, fresh porous silicon (PSi) nanoparticles were obtained.
[0063] (2) The same method as step (2) of Example 1 is used to prepare porous silicon loaded with palladium-platinum alloy nanozymes, wherein the porous silicon is the porous silicon nanoparticles obtained in step (1).
[0064] Figure 1 The attenuated total reflection infrared spectra of different silicon materials (porous silicon, peroxidized porous silicon, weakly oxidized porous silicon, and silicon dioxide) show that the Si-H bonds of porous silicon are converted into Si-OH bonds after weak oxidation by PBS to obtain weakly oxidized porous silicon nanoparticles, which are manifested as the stretching vibration peak of the Si-H bond (2100cm -1 ) and bending vibration peak (630cm -1 ) almost completely disappeared, and at the same time, the stretching vibration peak of the Si-OH bond (3000-3700cm -1 ) is enhanced. In addition, the bending vibration peak of Si-Si bond (470 cm -1 ) intensity also increased, which may be due to the strengthening of Si-OH bonds and the increase in the vibration intensity of Si-Si bonds. In peroxidized porous silicon, the peaks belonging to the stretching vibration of Si-O-Si bonds (800 and 1100 cm -1) is further enhanced, and the peak intensity of Si-OH bond (3000-3700cm -1 ) is weakened, which can be explained by the fact that the Si-OH bonds are highly oxidized, forming a Si-O-Si cross-linked structure. At the same time, the Si-Si bonds (470 cm -1 ) peak disappears, and the peak at 436cm -1 The bending vibration peak of Si-O-Si bond appears at , which is due to the network reorganization after the Si-Si skeleton is oxidized to Si-O-Si, producing the same vibration mode as the Si-O-Si bond in SiO2. The above results show that the surface of weakly oxidized porous silicon nanoparticles is mainly composed of Si-OH, and the surface of overoxidized porous silicon is mainly composed of Si-O-Si-OH.
[0065] Figure 2 The transmission electron microscope (TEM) images of porous silicon loaded with palladium-platinum alloy nanozymes and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes are shown in Figure 1. The results show that both porous silicon and weakly oxidized porous silicon can in situ reduce palladium (II) salts and platinum (IV) salts to obtain two composites, porous silicon loaded with palladium-platinum alloy nanozymes and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes. However, the palladium-platinum alloy nanozymes encapsulated in weakly oxidized porous silicon (average size of about 5.2 nm) are more evenly distributed than the palladium-platinum alloy nanozymes encapsulated in porous silicon.
[0066] Performance Test:
[0067] (1) Photothermal performance test of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0068] Porous silicon, weakly oxidized porous silicon (prepared in step (1) of Example 1), porous silicon loaded with palladium-platinum alloy nanozyme (prepared in comparative example 1), and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozyme (prepared in step (2) of Example 1) were placed in 1.5 mL centrifuge tubes and illuminated with near-infrared light (808 nm, 1.0 W / cm 2 ) for 5 minutes, and a thermal imager (FLIR ONE Pro, FLIR Systems, USA) was used to record the temperature changes of the solution during the illumination process (e.g. Figure 3 (as shown in Figure a).
[0069] We also measured the Pd-Pt alloy nanozymes loaded on weakly oxidized porous silicon (400 μg / mL) at different near-infrared laser power densities (0.5, 0.7, and 1.0 W / cm 2 ) under the photothermal response (such as Figure 3In addition, to evaluate the photothermal stability, the weakly oxidized porous silicon loaded with PdPt alloy nanozymes was exposed to near-infrared irradiation for 5 minutes and then the light source was removed, while the temperature change during cooling was monitored. Five repeated heating and cooling cycles were performed as described above (as shown in Figure 2b). Figure 3 (as shown in Figure c).
[0070] Figure 3 Figure a in the middle is the photothermal response curves of the control group, porous silicon, weakly oxidized porous silicon, porous silicon loaded with palladium-platinum alloy nanozymes, and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes; Figure b is the photothermal response curve of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes after being irradiated with lasers of different current densities; Figure c is the temperature change curve of weakly oxidized porous silicon loaded with nanozymes after being exposed to five near-infrared light irradiation-cooling cycles. Figure 3 The photothermal response performance of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes was investigated. As shown in Figure a, after 5 minutes of near-infrared laser irradiation at 808nm, the temperature of the control solution remained almost unchanged, and the temperature of the porous silicon and weakly oxidized porous silicon solutions only increased by about 3°C. The temperature of porous silicon loaded with palladium-platinum alloy nanozymes and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes increased significantly, but the temperature of the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes (59.5°C) was slightly higher than that of the porous silicon group loaded with palladium-platinum alloy nanozymes (58°C). In addition, as shown in Figure b, the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes showed a temperature rise behavior that depended on the laser power. As shown in Figure c, after five cycles of near-infrared light irradiation, the temperature rise value of the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes remained basically unchanged, indicating that it has good near-infrared photothermal conversion stability.
[0071] (2) Determination of catalase-like (CAT) activity of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0072] A portable dissolved oxygen meter was used to quantify the oxygen content produced by different materials during the catalytic process (e.g. Figure 4 The weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes (400 μg / mL) was mixed with different concentrations of H2O2 (0, 3, 6, 12, 18 mM) in PBS buffer (pH = 6.5), and then the real-time production of oxygen was monitored within 5 minutes with or without near-infrared irradiation (as shown in Figure a). Figure 4 The initial reaction temperature of the reaction system was set to 37°C, and the near-infrared laser power was controlled (0.5 W / cm 2 ) to ensure that the temperature of the reaction system reaches about 42.5°C. The initial reaction rate (V0) of various materials at different H2O2 concentrations is obtained based on the real-time change curve of oxygen content. m / Vmax +1 / V max and the double reciprocal curve, the Michaelis constant (K m ) and the maximum reaction rate (V max The above method was also used to analyze the CAT-like activity of the porous silicon-based nanozyme complex when heated to 42.5°C under near-infrared light irradiation (e.g. Figure 4 (as shown in Figure d).
[0073] Figure 4 The catalase (CAT) activity of different materials was investigated. Materials with CAT-like activity can catalyze the decomposition of H2O2 to produce O2. As shown in Figure a, the porous silicon loaded with palladium platinum alloy nanozymes and the weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes can catalyze the decomposition of H2O2 to produce O2, but the amount of O2 produced by the weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes is significantly higher than that of the porous silicon loaded with palladium platinum alloy nanozymes.
[0074] The characteristic parameter Michaelis constant (K) used to evaluate the performance of nanozymes was obtained by steady-state kinetic calculation. m ) and the maximum reaction rate (V max ). m The value represents the binding ability of nanozymes with reaction substrates, K m The lower the value, the easier it is for the nanozyme to bind to the substrate. max The value represents the ability of nanozyme to catalyze the reaction. max The larger the value, the faster the nanozyme catalysis reaction proceeds. max / K m The value can reflect the catalytic efficiency of the enzyme. Figure b shows the K of the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme. m The K value (17.00 mM) is lower than that of the porous silicon supported by the palladium-platinum alloy nanozyme. m value (25.62mM), the V max Value (10.71×10 -7 M / s) is higher than the V of the porous silicon supported by the Pd-Pt alloy nanozymes. max Value (7.987×10 -7 M / s). Pd-Pt alloy nanozymes loaded on weakly oxidized porous silicon (6.303×10 -5 / s) catalytic efficiency (V max / K m ) is a porous silicon supported by palladium-platinum alloy nanozymes (3.118×10 -5 / s) is twice as much. Therefore, the weakly oxidized porous silicon loaded with PdPt alloy nanozymes is more conducive to alleviating the hypoxia of TME than the porous silicon loaded with PdPt alloy nanozymes.
[0075] As shown in Figure c, under low-power near-infrared laser irradiation, the CAT-like activity of porous silicon supported by PdPt alloy nanozymes and weakly oxidized porous silicon supported by PdPt alloy nanozymes was further improved, but the catalytic efficiency of porous silicon supported by PdPt alloy nanozymes (4.179×10 -5 / s) is still significantly lower than the catalytic efficiency of weakly oxidized porous silicon supported by palladium-platinum alloy nanozymes (7.825×10 -5 / s).
[0076] In addition, the effect of the pore structure of weakly oxidized porous silicon on the activity of the nanozymes loaded inside was also investigated. The results in Figure d show that the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes was immersed in a weakly alkaline PBS solution (pH = 7.4) for 24 hours to collapse the pores of the weakly oxidized porous silicon, and the palladium-platinum alloy nanozymes with the weakly oxidized porous silicon carrier removed were obtained. Compared with the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes, the K m The value (28.29mM) increased significantly, V max Value (7.027×10 -7 M / s) decreased, and the catalytic efficiency (2.484×10 -5 / s) decreased by 60%, indicating that the presence of weakly oxidized porous silicon channels enhanced the CAT-like activity of the internally loaded PdPt alloy nanozymes.
[0077] (3) Determination of oxidase-like (OXD) activity of weakly oxidized porous silicon loaded with Pd-Pt alloy nanozymes
[0078] With or without near-infrared laser irradiation (0.5 W / cm 2 ) under the condition of 3,3',5,5'-tetramethylbenzidine (TMB) as substrate, in PBS buffer (pH = 6.5) containing porous silicon, weakly oxidized porous silicon, PdPt alloy nanozyme-loaded porous silicon or PdPt alloy nanozyme-loaded weakly oxidized porous silicon (400 μg / mL). The kinetic parameters (Michaelis constant (K m ) and the maximum reaction rate (V max )) As above, it is calculated by the Michaelis equation and the double reciprocal curve (such as Figure 5 shown).
[0079] Figure 5 It is shown that in TME, oxidase-like enzymes (OXD) can convert O2 into superoxide radicals (·O2 - The OXD-like activity of different materials was studied using 3,3',5,5'-tetramethylbenzidine (TMB) as a colorimetric reagent. TMB can be oxidized by ·O2 -Oxidation generates a blue product (oxTMB), which has a characteristic UV-visible absorption peak at 652nm. Figure 5 As shown in Figure a, both the porous silicon loaded with palladium-platinum alloy nanozymes and the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes can oxidize TMB to develop color, and the absorbance value of the weakly oxidized porous silicon system loaded with palladium-platinum alloy nanozymes is higher ( Figure 5 a) According to Figure 5 Steady-state kinetic analysis in Figure b shows the K of the porous silicon supported by the palladium-platinum alloy nanozyme. m The value is 0.4447mM, V max The value is 1.336×10 -8 M / s,V max / K m The value is 3.005×10 -5 / s, K of Pd-Pt alloy nanozymes loaded on weakly oxidized porous silicon m The value is 0.2576mM, V max The value is 1.713×10 -8 M / s,V max / K m The value is 6.649×10 -5 / s. Therefore, the substrate adsorption capacity, catalytic reaction rate and catalytic efficiency of the weakly oxidized porous silicon loaded with PdPt alloy nanozymes are significantly higher than those of the porous silicon loaded with PdPt alloy nanozymes. In addition, low-power near-infrared irradiation can improve the porous silicon (K m The value is 0.1993mM, V max The value is 1.751×10 -8 M / s,V max / K m The value is 5.018×10 -5 / s) and Pd-Pt alloy nanozymes supported on weakly oxidized porous silicon (K m The value is 0.1853mM, V max The value is 2.139×10 -8 M / s,V max / K m The value is 11.54×10 -5 / s) of OXD-like activity, but the catalytic performance of weakly oxidized porous silicon supported by palladium-platinum alloy nanozymes as OXD-like is still better than that of porous silicon supported by palladium-platinum alloy nanozymes ( Figure 5 As shown in Figure c). Figure 5 As shown in Figure d, the catalytic efficiency of the palladium-platinum alloy nanozyme without the weakly oxidized porous silicon support (2.523×10 -5 / s) is significantly lower than that of the weakly oxidized porous silicon loaded with PdPt alloy nanozymes, which confirms that the pore structure of weakly oxidized porous silicon can improve the OXD-like activity of the loaded PdPt alloy nanozymes.
[0080] (4) Determination of peroxidase-like (POD) activity of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0081] The peroxidase-like activity was determined by TMB colorimetric reaction in the presence of H2O2. Briefly, Pd-Pt alloy nanozymes loaded with weakly oxidized porous silicon (400 μg / mL), TMB (0.5 mM) and H2O2 (3.3 mM) were incubated with or without near-infrared stimulation (0.5 W / cm 2 The mixture was mixed with PBS buffer (pH=6.5) and reacted for 5 minutes, and then the absorbance of the above solution was recorded. The Michaelis constant (K) at normal physiological temperature (37°C) and near-infrared irradiation-induced temperature of about 42.5°C was determined using the Michaelis equation and the double reciprocal curve. m ) and the maximum reaction rate (V max )(like Figure 6 shown).
[0082] Figure 6 The POD-like properties of different materials were investigated. The POD-like properties of the materials were studied using a colorimetric reaction based on 3,3',5,5'-tetramethylbenzidine (TMB). Generally speaking, POD can catalyze the decomposition of H2O2 to produce ·OH, and ·OH can oxidize TMB to generate an oxidation product with characteristic absorption at 652nm. Porous silicon, weakly oxidized porous silicon, porous silicon loaded with palladium-platinum alloy nanozymes, or weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes were added to a mixed solution containing H2O2 and TMB, and the reaction was continued for 5 minutes at a normal physiological temperature of 37°C. Compared with the porous silicon group and the weakly oxidized porous silicon group, the absorbance values of the porous silicon group loaded with palladium-platinum alloy nanozymes and the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes at 652nm were significantly increased, among which the absorbance value of the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes was higher than that of the porous silicon group loaded with palladium-platinum alloy nanozymes (Figure a). Through steady-state kinetic analysis (Fig. b), it was found that the K of the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme when H2O2 was used as the substrate m The value is 0.5559 mM, which is much lower than the K of the porous silicon supported by the palladium-platinum alloy nanozyme. m Value (1.080mM). V of weakly oxidized porous silicon supported by palladium-platinum alloy nanozymes max Value (5.851×10 -8 M / s) is slightly higher than the V of the porous silicon supported by the Pd-Pt alloy nanozymes. max Value (5.537×10 -8 M / s, while the weakly oxidized porous silicon supported by palladium-platinum alloy nanozymes (10.53×10 -5 / s) was significantly better than the Pd-Pt alloy nanozyme-supported porous silicon (5.126×10 -5 / s). This indicates that the weakly oxidized porous silicon supported by the PdPt alloy nanozyme has a better POD-like activity than the porous silicon supported by the PdPt alloy nanozyme. The mild thermal stimulation induced by near-infrared irradiation can further improve the catalytic efficiency of the porous silicon system supported by the PdPt alloy nanozyme (K m =0.8194mM, V max =6.606×10 -8 M / s) and Pd / Pt alloy nanozymes supported on weakly oxidized porous silicon system (K m =0.4496mM, V max =6.748×10 -8 M / s) substrate adsorption capacity and catalytic reaction rate (Fig. c). It is worth noting that even with the introduction of mild photothermal stimulation, the POD-like performance of the weakly oxidized porous silicon supported by the PdPt alloy nanozyme is still better than that of the porous silicon supported by the PdPt alloy nanozyme. In addition, the PdPt alloy nanozyme (3.900×10 -5 / s) is only 37% of that of the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme, which indicates that the pore confinement effect of weakly oxidized porous silicon can promote the POD-like activity of the loaded palladium-platinum alloy nanozyme (Figure d).
[0083] (5) Determination of glutathione oxidase-like (GSHOx) activity of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0084] The GSHOx-like activity of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes was measured by a colorimetric method based on 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB). The reaction product of DTNB has a characteristic absorption peak at 412 nm, and the remaining amount of GSH in the reaction system can be evaluated by monitoring the absorbance value at 412 nm. Steady-state kinetic studies were performed at normal physiological temperature (37°C) and mild photothermal temperature (~42.5°C induced by low-power near-infrared laser), respectively. Weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes (400 μg / mL), GSH (0.2 mM) and DTNB (200 μg / mL) were added to PBS buffer solution (pH = 6.5), and the absorbance value (412 nm) of the mixture was recorded after 5 minutes of reaction. Different concentrations of GSH were added to the above system, and the Michaelis constant (K) of the simulated GSHOx was calculated by steady-state kinetic analysis. m ) and the maximum reaction rate (V max )(like Figure 7 shown).
[0085] Figure 7The GSHox-like properties of different materials were evaluated. The reaction product (TNB) of DTNB and GSH has a typical absorption peak at a wavelength of 412nm, so the remaining amount of GSH in the reaction system can be monitored by the change of the TNB absorption peak with the reaction time. Different materials were added to a solution containing DTNB and TNB, and the absorbance value of the mixed solution was measured after the reaction was continued at 37°C for 5 minutes. Compared with the system with porous silicon and weakly oxidized porous silicon added, the absorbance value belonging to TNB at 412nm in the system containing porous silicon loaded with palladium-platinum alloy nanozymes and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes decreased significantly (Figure a). Steady-state kinetic analysis (Figure b) showed that when GSH was used as the substrate, the K of porous silicon loaded with palladium-platinum alloy nanozymes was m The value is 0.3516mM, V max The value is 3.283×10 -7 M / s,V max / K m The value is 9.337×10 -4 / s. K of Pd-Pt alloy nanozymes loaded on weakly oxidized porous silicon m The value is 0.3120mM, V max The value is 5.048×10 -7 M / s,V max / K m The value is 16.18×10 -4 / s, proving that the GSHOx-like activity of weakly oxidized porous silicon supported by palladium-platinum alloy nanozymes is better than that of porous silicon supported by palladium-platinum alloy nanozymes. Figure 7 As shown in Figure c, when subjected to mild photothermal stimulation, the ability of the PdPt alloy nanozyme-loaded porous silicon and the PdPt alloy nanozyme-loaded weakly oxidized porous silicon to consume GSH was improved, among which the PdPt alloy nanozyme-loaded weakly oxidized porous silicon (21.93×10 -4 / s) is still significantly higher than that of the porous silicon supported by Pd-Pt alloy nanozymes (14.73×10 -4 / s), proving that mild photothermal stimulation can effectively enhance the GSHOx-like activity of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes. Figure 7 As shown in Figure d, after the pores of weakly oxidized porous silicon were destroyed, the catalytic efficiency of the Pd-Pt alloy nanozyme as a GSHOx-like nanozyme after the weakly oxidized porous silicon carrier was removed dropped to 7.422×10 -4 / s, which further indicates that weakly oxidized porous silicon has a pore confinement effect, which can enhance the GSHOx-like activity of the nanozymes loaded inside.
[0086] Figure 8The electron state density (DOS) diagram of the porous silicon supported by the palladium-platinum alloy nanozyme (a) and the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme (b). The results show that compared with the porous silicon supported by the palladium-platinum alloy nanozyme, the weakly oxidized porous silicon supported by the palladium-platinum alloy nanozyme has a higher Fermi level (E f ), indicating that there is a more efficient electron transfer at the interface between the weakly oxidized porous silicon and the palladium-platinum alloy nanozyme. This is because the highly electronegative Si-Si-OH bonds on the surface of weakly oxidized porous silicon can form chemical bonds and electronic coupling with precious metals, thereby enhancing the electronic interaction between the weakly oxidized porous silicon and the palladium-platinum alloy nanozymes, and ultimately forming a stable semiconductor-metal heterojunction. In contrast, the Si-Si-H bonds on the surface of porous silicon have a weaker interaction with the palladium-platinum alloy nanozymes, so the stability and electron transfer ability of the heterojunction are not as good as those of the weakly oxidized porous silicon system loaded with palladium-platinum alloy nanozymes. Based on this calculation, it is concluded that the d-band center (-0.39 eV) of the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes is closer to E than the d-band center (-0.72 eV) of the porous silicon loaded with palladium-platinum alloy nanozymes. f (0eV), which is because the Pd-Pt alloy nanozyme E f The electrons at the d-band can be more effectively transferred to the weakly oxidized porous silicon, increasing the unfilled degree of the d orbital and causing the d-band center to move upward. The upward shift of the d-band center can more effectively donate electron density to the antibonding orbital of oxygen, reduce the strength of the OO bond, and promote the oxidation of ·O2 - At the same time, the palladium-platinum alloy nanozyme E f The abundant cavities at these sites can participate in enzyme-like catalytic reactions to oxidize different substrates.
[0087] (6) Cell culture
[0088] Mouse breast cancer cells (4T1) were purchased from Fenghui Biotechnology Co., Ltd., China, and cultured in RPMI-1640 medium containing 10% fetal bovine serum and 1% penicillin (100 units / ml)-streptomycin (100 μg / ml) in an incubator set at 37°C with 5% CO2.
[0089] (7) Cytotoxicity
[0090] CellTiter-Lumin kit (Beyond Biotech, China) was used to evaluate the cytotoxicity of different materials on 4T1 cells. 4T1 cells (8 × 10 3) were inoculated into a white 96-well plate and washed with PBS after overnight culture. Fresh RPMI-1640 medium containing four materials at different concentrations (0, 80, 160, 240, 320, 400 μg / mL) was then added and cultured for 24 hours. Celltiter-Lumin reagent (100 μL) was then added to each well and shaken for 10 minutes, and the chemiluminescent signal was measured using a microplate reader (Thermo Scientific 5250040, USA). In addition, the effects of different materials on cytotoxicity under mild photothermal stimulation were also studied. As described above, different materials were added to the inoculated cells and cultured for 4 hours, and then the cells were placed under 808nm near-infrared light irradiation (0.5W / cm 2 ) for 5 minutes, and then cultured for 20 hours, and then the cell viability was measured using the same procedure as above ( Fig. 9 shown).
[0091] Fig. 9 The anti-breast cancer cell (4T1) performance of different materials in vitro was investigated. Fig. 9 As shown, under low-power near-infrared light irradiation, with the increase of the concentration of porous silicon and weakly oxidized porous silicon in the reaction system, the viability of 4T1 cells remained basically unchanged. However, the porous silicon loaded with palladium platinum alloy nanozymes and the weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes showed obvious concentration dependence on the viability of 4T1 cells. At the same concentration (400μg / mL), the survival rate of 4T1 cells treated with weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes (18%) was lower than that of 4T1 cells treated with porous silicon loaded with palladium platinum alloy nanozymes (40%), which proves that weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes can more effectively inhibit the growth of tumor cells than porous silicon loaded with palladium platinum alloy nanozymes.
[0092] (8) Intracellular oxygen detection
[0093] 4T1 cells seeded in 24-well plates were cultured overnight in an oxygen-deficient environment (1% O2 and 5% CO2). After adding different materials, the culture was continued for 2 hours, and then near-infrared stimulation (0.5 W / cm 2 , 5 minutes). After adding 2 μM tris(4,7-diphenyl-1,10-phenanthroline) dichlororuthenium(II) ([Ru(dpp)3]Cl2) probe and culturing for 6 hours, the cell fluorescence was recorded by inverted fluorescence microscopy (e.g. Fig.10 shown).
[0094] Fig.10The oxygen generation in 4T1 cells after treatment with different materials was evaluated. It was observed that among the five different treatment groups, the fluorescent oxygen probe showed the weakest red fluorescence in the weakly oxidized porous silicon group loaded with palladium platinum alloy nanozymes, indicating that the weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes can most effectively reverse the hypoxic environment of TME. In addition, the quenching of the red fluorescence signal of 4T1 cells treated with weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes under mild photothermal stimulation was more obvious, proving that more O2 was produced. The above results indicate that weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes exhibits mildly photothermally enhanced CAT-like activity in tumor cells.
[0095] (9) Intracellular ROS detection
[0096] 4T1 cells were seeded in 24-well culture plates and treated as described above. Reactive oxygen probe (DCFH-DA) was added and incubated for 30 minutes, and then washed three times with serum-free RPMI-1640 medium to fully remove residual DCFH-DA and record fluorescence images (such as Fig.11 shown).
[0097] Fig.11 The changes in ROS levels in 4T1 cells after treatment with different materials were tested to evaluate the POD-like performance of different materials at the cellular level. First, the generation of ·OH in 4T1 cells after adding different materials was investigated without near-infrared light irradiation. Fig.11 As shown in the figure, compared with the porous silicon group, the weakly oxidized porous silicon group and the porous silicon group loaded with palladium-platinum alloy nanozymes, the strongest green fluorescence was observed in the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes, proving that the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes can also be used as POD-like nanozymes at the cellular level to catalyze the decomposition of H2O2 to produce a large amount of ·OH for killing tumor cells. Secondly, after applying near-infrared light irradiation, the green fluorescence of the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes was further enhanced, indicating that mild photothermal stimulation can enhance the POD-like performance of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes in 4T1 cells.
[0098] (10) Detection of intracellular glutathione levels
[0099] 4T1 cells (1×10 5After culturing for 12 hours, porous silicon, weakly oxidized porous silicon, porous silicon loaded with palladium-platinum alloy nanozymes, and weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes were added respectively, and the culture was continued for 8 hours. The GSH and GSSG levels in tumor cells after different treatments were determined using the protocol in the GSH / GSSG kit (Biyuntian Biotechnology Co., Ltd.). In addition, after culturing for 2 hours, the porous silicon group loaded with palladium-platinum alloy nanozymes and the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes were irradiated with near-infrared laser for 5 minutes, and the culture was continued for 6 hours before detection (such as Fig.12 shown).
[0100] Fig.12 The GSHOx-like performance of different materials in 4T1 cells was evaluated. Compared with the control group, the ratio of glutathione to oxidized glutathione in the 4T1 cells of the porous silicon group and the weakly oxidized porous silicon group remained basically unchanged. However, in the 4T1 cells with the addition of the porous silicon loaded with palladium-platinum alloy nanozymes and the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes, the ratio of glutathione to oxidized glutathione decreased, among which the ratio of the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes decreased more significantly, proving that the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes can oxidize the glutathione in the cells more effectively and has GSHOx-like performance.
[0101] (11) Intracellular malondialdehyde (MDA) detection
[0102] 4T1 cells were inoculated into 6-well plates, treated with different methods, and completely lysed using Western Lysis Buffer at 4°C. The supernatant was then collected by centrifugation at 10,000 g for 10 minutes. The MDA content in different samples (e.g. Fig.13 shown).
[0103] Fig.13 The changes in malondialdehyde levels in tumor cells after treatment with different materials were investigated. When no near-infrared light stimulation was applied, the expression level of malondialdehyde (MDA) in 4T1 cells treated with weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes was the lowest, proving that weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes induced the accumulation of a large amount of lipid peroxides (LPO) by accumulating ROS and consuming GSH, indicating that weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes can induce the occurrence of ferroptosis. After low-power light stimulation, the MDA content in 4T1 cells in the porous silicon group loaded with palladium-platinum alloy nanozymes and the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes was further reduced, but the MDA level in the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes was still significantly lower than that in the porous silicon group loaded with palladium-platinum alloy nanozymes, proving that mild photothermal stimulation can induce weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes to produce ferroptosis reactions more efficiently.
[0104] (12) Detection of intracellular heat shock proteins (HSPs) levels
[0105] 4T1 cells (1×105 cells per well) were placed in a 6-well culture plate. The HSP70 test was divided into two groups. The first group was not irradiated with near-infrared light, but only different materials were applied and cultured for 8 hours. The second group was added with different materials and cultured for 2 hours, and then near-infrared laser (0.5 W / cm 2 , 5 minutes) for 5 minutes. The culture was continued for 6 hours, and then the cells were digested with trypsin and collected. The proteins were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to a polyvinylidene fluoride (PVDF) membrane. After blocking with 5% milk, the membrane was incubated with the primary antibody at 4°C for 12 hours and then incubated with the secondary antibody for another hour. Finally, the membrane was exposed to the ECLplus imaging system to observe the protein bands (such as Fig.14 shown).
[0106] Fig.14 The changes in the levels of HSPs in tumor cells after treatment with different materials were studied. It was observed that under the condition of mild photothermal stimulation, the level of HSP70 in the weakly oxidized porous silicon group loaded with palladium-platinum alloy nanozymes decreased significantly. This is because the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes with quadruple mimetic enzyme activity will produce a large amount of ROS and LPO in the process of inducing ferroptosis reaction, thereby inhibiting the expression of HSP70 and preventing the self-repair of HSP70, making 4T1 tumor cells more sensitive to mild photothermal therapy.
[0107] (13) Stability study of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes
[0108] After one month of storage at room temperature and dry conditions, the freshly prepared PdPt alloy nanozyme-loaded weakly oxidized porous silicon or the PdPt alloy nanozyme-loaded weakly oxidized porous silicon after one month of storage was applied to 4T1 cells, and after four hours of culture, 808 nm light stimulation (1.0 W / cm2, 5 minutes) was applied, and then the cell viability was measured as described above (e.g. Fig.15 shown).
[0109] Fig.15 The storage stability of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes was investigated. Under near-infrared light stimulation, the growth inhibition rate of 4T1 cells loaded with weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes after one month of storage can still be maintained above 99.7%. The above results prove that weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes has good storage stability and potential in practical applications.
[0110] (14) Study on the anti-tumor properties of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes in vivo
[0111] BALB / c mice (5–6 weeks, female) were purchased from SLAC Laboratory Animal Co., Ltd. (China). All animal experiments were approved by the Experimental Animal Center of Zhejiang University and supervised by the Animal Ethics Committee of Zhejiang University (ZJU20240391). 4T1 cells (1×10 6 The 4T1 tumor model was established. When the tumor volume grew to about 100 mm 3 The mice were randomly divided into three groups (four mice in each group): (i) saline + near-infrared light group; (ii) PdPt alloy nanozyme-loaded porous silicon + near-infrared light group; (iii) PdPt alloy nanozyme-loaded weakly oxidized porous silicon + near-infrared light group. The mice were injected with PBS, PdPt alloy nanozyme-loaded porous silicon, or PdPt alloy nanozyme-loaded weakly oxidized porous silicon solution into the tumor. Two hours after the injection, the mice were illuminated with an 808nm laser (0.5W / cm 2 , 5 minutes) irradiate the tumor area. Measure and record the weight and tumor volume of mice every two days. Tumor volume = 0.5 × tumor length × (tumor width)^2. After 14 days of different treatments, the mice were killed and the tumor tissues were taken out for photography and weighing, and the tumor growth inhibition rate (TGI) was calculated. TGI = (1-tumor weight of treatment group / tumor weight of control group) × 100% (such as Fig.16 shown).
[0112] Fig.16 The ability of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes to treat breast cancer in vivo was investigated. In vivo experiments showed that after 14 days of treatment, the tumors of mice in the group that was stimulated by only saline and near-infrared light grew in a completely uncontrollable manner. The tumor volume of mice in the group that was simultaneously exposed to porous silicon loaded with palladium-platinum alloy nanozymes and near-infrared light decreased, and the tumor growth trend was controlled to a certain extent, with a tumor growth inhibition rate (TGI) of 70.3%. It is worth noting that the tumor volume of mice in the group that was simultaneously exposed to weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes and near-infrared light was significantly reduced, with a TGI value of up to 90.0%, proving that with the assistance of low-power near-infrared light, weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes exhibits excellent anti-breast cancer effects in vivo.
[0113] (15) In vivo biodistribution study
[0114] In order to evaluate the accumulation and metabolism of weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes in vivo, a biodistribution study was conducted. Tumor-bearing mice were killed 1 day and 14 days after the above treatment, and the collected major organs and tumors were immersed in nitric acid for 24 hours for nitration. The pH value of the above solution was then adjusted to 6.5 and filtered with a filter membrane (0.45 μm). The contents of silicon, palladium, and platinum in each organ were calculated by ICP-OES analysis (e.g. Fig.17 shown).
[0115] Fig.17 According to the biodistribution analysis, palladium, platinum and silicon were present in the liver, spleen, lungs, kidneys and tumors of mice one day after administration, proving that the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes can enter the body circulation. After 14 days, the levels of palladium, platinum and silicon in tumors and major organs were greatly reduced, indicating that the biodegradable weakly oxidized porous silicon carrier allows the internally loaded palladium-platinum alloy nanozymes to be metabolized into orthosilicic acid and effectively excreted from the body. The above experimental results prove that the weakly oxidized porous silicon loaded with palladium-platinum alloy nanozymes has good biodegradability.
[0116] (16) Histological and pathological analysis
[0117] Tumor tissues and major organs of the sacrificed mice were immersed in 4% paraformaldehyde for 24 h, then embedded in paraffin and sectioned for H&E, TUNEL, Ki-67, HIF-1α, and HSP70 staining analysis (see Fig.18 shown).
[0118] Fig.18It was shown that the anti-tumor pathway of weakly oxidized porous silicon loaded by palladium-platinum alloy nanozymes was revealed by histopathological examination. H&E staining was performed on tumor sections of different treatment groups of palladium-platinum alloy nanozymes, and the most obvious tumor tissue damage was observed in the weakly oxidized porous silicon loaded by palladium-platinum alloy nanozymes + near-infrared light irradiation group. At the same time, terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) and Ki-67 detection showed that under low-power near-infrared light irradiation, weakly oxidized porous silicon loaded by palladium-platinum alloy nanozymes could kill tumor cells more effectively and inhibit their proliferation than porous silicon loaded by palladium-platinum alloy nanozymes. Immunofluorescence staining of HIF-1α showed that the oxygenation level of the weakly oxidized porous silicon loaded by palladium-platinum alloy nanozymes + near-infrared light irradiation group was the highest among the three groups, which was manifested as a sharp attenuation of red fluorescence. This is because the weakly oxidized porous silicon loaded by palladium-platinum alloy nanozymes has good CAT-like activity, which can reverse the hypoxic state of TME. In addition, the expression of HSP70 in the tumors of the group using weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes and near-infrared light irradiation was also suppressed to the greatest extent, indicating that weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes can induce ferroptosis reaction, thereby enhancing the mild photothermal therapy effect. In summary, in the in vivo experiment, weakly oxidized porous silicon loaded with palladium platinum alloy nanozymes has a stronger ability to inhibit tumor growth than porous silicon loaded with palladium platinum alloy nanozymes.
[0119] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A supported noble metal alloy nanozyme, characterized in that: It is composed of weakly oxidized porous silicon nanoparticles and noble metal alloy nanozymes loaded on the surface and in the pores of the nanoparticles. The weakly oxidized porous silicon nanoparticles are obtained by oxidizing porous silicon nanoparticles through phosphate buffer solution, deionized water, alkaline borate or phosphate solution.
2. The supported noble metal alloy nanozyme according to claim 1, characterized in that: The noble metal alloy nanozyme is selected from palladium-platinum noble metal alloy nanozyme, gold-silver noble metal alloy nanozyme or silver-palladium noble metal alloy nanozyme.
3. The supported noble metal alloy nanozyme according to claim 2, characterized in that: The noble metal alloy nanozyme is selected from palladium-platinum noble metal alloy nanozyme, and the Pd content in the weakly oxidized porous silicon of the supported noble metal alloy nanozyme is 80-85 μg / mg, and the Pt content is 35-50 μg / mg.
4. The supported noble metal alloy nanozyme according to claim 3, characterized in that: The mass ratio of palladium to platinum in the palladium-platinum alloy nanozyme is (2-2.5):
1.
5. The method for preparing the supported noble metal alloy nanozyme according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing porous silicon nanoparticles and phosphate buffer solution to obtain weakly oxidized porous silicon nanoparticles; (2) A palladium source, a platinum source, weakly oxidized porous silicon nanoparticles and water are mixed to perform an in-situ reduction reaction to obtain the loaded noble metal alloy nanozyme.
6. The method according to claim 5, characterized in that The pH value of the phosphate buffer solution is 7-7.4; The ratio of the porous silicon nanoparticles to the phosphate buffer solution is 1 g: (10-300) mL.
7. The method according to claim 5, characterized in that The reaction temperature of step (1) is 25°C-50°C.
8. The method according to claim 5, characterized in that The molar ratio of the palladium element in the palladium source to the platinum element in the platinum source is 1:(0.5-1.5).
9. The method according to claim 5, characterized in that The palladium source is selected from one or more of chloropalladic acid, palladium chloride, and sodium chloropalladate; The platinum source is selected from one or more of chloroplatinic acid, potassium chloroplatinate, and ammonium chloroplatinate.
10. Use of the supported noble metal alloy nanozyme according to any one of claims 1 to 4 or the supported noble metal alloy nanozyme prepared by the preparation method according to any one of claims 5 to 9 in the preparation of drugs for treating tumors.
Citation Information
Patent Citations
Nano enzyme with nanometer cage core of hollow gold-platinum alloy and shell of porous silicon dioxide, preparation method and application thereof
CN109358195A
Preparation method and application of porous silicon platinum nano-enzyme material
CN111744472A
Gallium ion and enzyme co-loaded antibacterial agent as well as preparation method and application thereof
CN115671266A
Graded porous silicon nano material and preparation method and application thereof
CN116395696A
Porous silicon-based nano-enzyme compound as well as preparation method and application thereof
CN117257942A